2023
DOI: 10.22541/essoar.169603551.19539639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying magma overpressure beneath a submarine caldera: A mechanical modeling approach to tsunamigenic trapdoor faulting near Kita-Ioto Island, Japan

Osamu Sandanbata,
Tatsuhiko Saito

Abstract: Submarine volcano monitoring is vital for assessing volcanic hazards but challenging in remote and inaccessible environments. In the vicinity of Kita-Ioto Island, south of Japan, unusual M~5 non-double-couple volcanic earthquakes exhibited quasi-regular repetition near a submarine caldera. Following the 2008 earthquake, a distant ocean bottom pressure sensor recorded a distinct tsunami signal. In this study, we aim to find a source model of the tsunami-generating earthquake and quantify the pre-seismic magma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Another series of abnormal tsunamis have recurrently taken place, almost every 10 years, due to M w 5.4–5.8 volcanic earthquakes at another submarine caldera, Sumisu Caldera (Figure 1c) (Kanamori et al., 1993; Satake & Kanamori, 1991), for which a submarine trapdoor faulting in the inflating caldera was proposed (Sandanbata et al., 2022); the same mechanism has been recently proposed for tsunamigenic earthquakes at two other submarine calderas: Curtis Caldera, New Zealand (Sandanbata et al., 2023), and Kita‐Ioto Caldera, Japan (Sandanbata & Saito, 2024). These submarine trapdoor faulting events are tsunamigenic but exhibit atypically inefficient seismic excitation (Sandanbata et al., 2021, 2022).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Another series of abnormal tsunamis have recurrently taken place, almost every 10 years, due to M w 5.4–5.8 volcanic earthquakes at another submarine caldera, Sumisu Caldera (Figure 1c) (Kanamori et al., 1993; Satake & Kanamori, 1991), for which a submarine trapdoor faulting in the inflating caldera was proposed (Sandanbata et al., 2022); the same mechanism has been recently proposed for tsunamigenic earthquakes at two other submarine calderas: Curtis Caldera, New Zealand (Sandanbata et al., 2023), and Kita‐Ioto Caldera, Japan (Sandanbata & Saito, 2024). These submarine trapdoor faulting events are tsunamigenic but exhibit atypically inefficient seismic excitation (Sandanbata et al., 2021, 2022).…”
Section: Discussionmentioning
confidence: 64%
“…However, the Izu‐Bonin region hosts tens of volcano islands and submarine volcanoes, and active back‐arc rift systems (Kodaira et al., 2007), implying various types of potential tsunami hazards. As discussed above, M > 5 trapdoor faulting earthquakes can cause notable tsunamis from submarine calderas (Sandanbata et al., 2022; Sandanbata & Saito, 2024). An M w 6.4 normal faulting earthquake on 24 October 2006 in a region between Sofugan volcano and Nichiyo Seamount (Figure 1c) also generated about 10‐cm tsunamis (Japan Meteorological Agency, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Αt active volcanic calderas, various mechanisms can cause significant vertical deformation capable of exciting tsunamis (e.g., Acocella, 2007; Cole et al., 2005; Lipman, 1997). Although we cannot determine the exact process at the caldera due to the limitation of the data set we used, a possible candidate to explain the seafloor uplift is a trapdoor faulting, or sudden slip of the intra‐caldera ring fault caused by overpressurization of its underlying magma reservoir, which can cause sudden uplift of the caldera (Sandanbata et al., 2022; Sandanbata & Saito, 2024; Zheng et al., 2022). It has been often reported that submarine trapdoor faulting excites significant tsunamis, which have larger amplitudes than those expected from their seismic magnitudes (e.g., Fukao et al., 2018; Sandanbata et al., 2022; Sandanbata et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Focal mechanisms representing moment tensors are plotted with a MATLAB code of focalmech (Conder, 2019). The data of the source model proposed for the main results in this study (Figure 3) can be obtained from an open-access repository of Zenodo (Sandanbata & Saito, 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%